Dynamic Tensile Test of Granite and Its Tensile Sensitivity. (23rd October 2020) - Man, Ke; Song, Zhifei; Liu, Xiaoli
Abstract : Through the dynamic splitting tensile test under various loading rates, different mechanical parameters have been analyzed; not only the dynamic peak stress but also the dynamic peak strain has a good linear relationship with the strain rate. The tensile sensitivity obtained from the dynamic tensile test increases with strain rate gradually, and it shows a nearly linear relation, which fully indicates that the granite specimen is a strain rate sensitive material. Moreover, with the numerical simulation, the damage area of the specimen is consistent with the actual failure mode of the specimen. Furthermore, the influenced factor on the dynamic tensile strength is discussed, which illuminates that the most fundamental reason of the rate effect is that the stress wave velocity is faster than the crack propagation velocity in the specimen during the impact process.